Role of Type I and II Interferons in Colorectal Cancer and Melanoma - Di Franco, Simone; Turdo, Alice; Todaro, Matilde; Stassi, Giorgio (Frontiers in Immunology, 2017)
Cancer can be considered an aberrant organ with a hierarchical composition of different cell populations. The tumor microenvironment, including the immune cells and related cytokines, is crucial during all the steps of tumor development. In particular, type I and II interferons are involved in a plethora of mechanisms that regulate immune responses in cancer, thus balancing immune escape versus immune surveillance. Interferons are involved in both the direct and indirect regulation of cancer cell proliferation and metastatic potential. The mutational background of genes involved in interferons signaling could serve as a prognostic biomarker and a powerful tool to screen cancer patients eligible for checkpoint blocking therapies. We herewith describe the latest findings regarding the contribution of interferons in colorectal cancer and melanoma by researching their dual role as either tumor promoter or suppressor, in diverse tumor types and microenvironmental context. We are reporting the most innovative and promising approaches of interferon-based therapies that have achieved considerable outcomes inclinical oncology practice and explain the possible mechanisms responsible for their failure.